Lactate profiles in blood and sweat during exercise and heat induced sweating - Sirisinghe, R.G.; Singh, Rabindarjeet; Singh, Harbindar Jeet (1999)
Blood lactate levels and sweat lactate excretion were determined during exercise and subsequently during heat induced sweating, in the same subjects in an attempt to investigate the contribution of blood lactate to the sweat lactate excretion. Eighteen male volunteers of ages 15- 32 participated in the study. Exercise was performed on a cycle ergometer and involved a stepwise increase in workload until exhaustion. A passenger van with shutters up parked in the afternoon sun was used to create a warm environment-for heat-induced sweating. Both exercise (0.017 ± 0.001 L/min/m2) and the warm environment (0.013 ± 0.001 /min/m2) induced comparable rates of sweating. Pretest blood lactate levels were similar before exercise (2.2 ± 0.16 mmol/L) and heat test (1.9 ± 0.12 mmol/L). However, blood lactate levels during exercise (10.4 ± 0.42 mmol/L) were significant higher than levels during heat induced sweating (1.9 ± 0.10 mmol/L) (P < 0.001). Sweat lactate excretion during exercise (1.03 ± 0.11 mmol/min/m2) was significantly greater than sweat lactate excretion during heat induced sweating, (0.54 ± 0.04 mmol/min/m2) in spite of comparable volumes of sweat production.During heat induced sweating, sweat lactate excretion increased with increased sweat rates and the correlation a significant (r • 0.48) (p < 0.001). These results demonstrate that raised blood lactate levels during exercise contribute significantly to sweat lactate excretion. Sweat gland metabolism also contributes to sweat lactate excretion.The results cannot quantify the relative contributions of these two factors. Such quantification will necessitate further studies in the future. Whatever these respective contributions may be, sweat lactate excretion is probably not a sufficiently reliable index of aerobic capacity, to be recommended as a routine measurement because of its variability with varying sweat gland metabolism.